2023
DOI: 10.3390/nu15214549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus kefiri, in Conjunction with PENS T6 and a Hypocaloric Diet, on Weight Loss, Hypertension and Laboratory Glycemic and Lipid Profile

Jaime Ruiz-Tovar,
Carolina Llavero,
Maria-Encarnacion Fernandez-Contreras

Abstract: The pathogenesis of obesity has been linked to alterations in gut microorganisms. The aim of this study was to investigate the effect of Lactobacillus kefiri, together with PENS T6 and a hypocaloric diet, on weight loss, hypertension and laboratory glycemic and lipid profile. A prospective non-randomized study was conducted involving adult patients with a body mass index (BMI) > 30 kg/m2. Patients were divided into two groups: those undergoing PENS-T6 and hypocaloric diet (PENS-Diet Group) and those undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Ruiz-Tovar and collaborators conducted a prospective non-randomized study to investigate the effect of L. kefiri and a hypocaloric diet on cardiovascular risk markers. The addition of L. kefiri to a low-calorie diet increased weight loss and further improved the glycemic and lipid profile and also caused a further improvement in obesity-associated dysbiosis, mainly by increasing the muconutritive and regulatory (e.g., Bifidobacterium spp., Akkermansia muciniphila) microbiome, and decreasing the Firmicutes/Bacteroidetes ratio (Ruiz-Tovar et al, 2023). In addition, recent studies demonstrated that chronic consumption of probiotics, oats, soymilk, and apples may decrease diastolic blood pressure, triglycerides, total cholesterol, and insulin levels and significantly increase high-density lipoprotein cholesterol, beneficially affecting cardiometabolic health (Naseri et al, 2022;Pavlidou et al, 2022;Hasanpour et al, 2023;Pushpass et al, 2023;Zarezadeh et al, 2023).…”
Section: Probiotics In Cardiovascular and Cerebrovascular Diseasesmentioning
confidence: 99%
“…Ruiz-Tovar and collaborators conducted a prospective non-randomized study to investigate the effect of L. kefiri and a hypocaloric diet on cardiovascular risk markers. The addition of L. kefiri to a low-calorie diet increased weight loss and further improved the glycemic and lipid profile and also caused a further improvement in obesity-associated dysbiosis, mainly by increasing the muconutritive and regulatory (e.g., Bifidobacterium spp., Akkermansia muciniphila) microbiome, and decreasing the Firmicutes/Bacteroidetes ratio (Ruiz-Tovar et al, 2023). In addition, recent studies demonstrated that chronic consumption of probiotics, oats, soymilk, and apples may decrease diastolic blood pressure, triglycerides, total cholesterol, and insulin levels and significantly increase high-density lipoprotein cholesterol, beneficially affecting cardiometabolic health (Naseri et al, 2022;Pavlidou et al, 2022;Hasanpour et al, 2023;Pushpass et al, 2023;Zarezadeh et al, 2023).…”
Section: Probiotics In Cardiovascular and Cerebrovascular Diseasesmentioning
confidence: 99%